Assessment of building maintenance management in public boarding schools - Nik Elyna Myeda,; Nur Azziati Mohd Zambli, (Penerbit Universiti Kebangsaan Malaysia, 2018)
There are defects occurred in the school facilities that were reported from time to time in the newspapers. Worst, some of the defects had caused death to the occupants. It is claimed that maintenance management practice is one of the reasons that caused the problems and could be one of the reasons that impede the successful implementation of a plan in Malaysia Education Development Plan 2013-2025, which is to provide conducive learning and teaching environment at the schools. Previous researchers have proved that the maintenance management practice is related to the occupants’ satisfaction and performance. Previous studies cover maintenance management practice and occupants’ satisfaction of daily schools but none focuses on the public boarding schools. Hence, this research aims to assess the current maintenance management practice in public boarding schools. This research was conducted using interview and questionnaire survey. It is found that the selected case studies of the public schools generally practice unplanned maintenance and the rated occupants’ satisfaction is at average level. This research also signifies that there is a significant relationship between maintenance management practice and occupant satisfaction.